The Regulation of Potassium Absorption in Barley Roots - Glass, Anthony (1975)
The dynamics of changes in K(+) influx across the plasmalemma and of internal K(+) concentrations [K(+)](1) of intact barley (Hordeum vulgare) roots were examined as the roots were converted from `high-salt' to `low-salt' roots. Following the transfer of plants grown in 0.5 mm CaSO(4) solutions plus various concentrations of KCl to 0.5 mm CaSO(4) solutions, influx rates increased and internal K(+) concentrations declined as a function of time and the initial K(+) status of the tissue. The relationship between plasmalemma influx and [K(+)](1) was examined over a wide range of [K(+)](1) values by growing intact plants in various concentrations of KCl. Plasmalemma influx was inversely correlated with the square of [K(+)](1). A model for the regulation of plasmalemma influx by [K(+)](1) is considered.